Optimalisasi Layanan Akademik Melalui Aplikasi Berbasis Visual 6.0 Untuk Meningkatkan Kualitas Layanan Administrasi - Hendriansyah, Hendriansyah; Alam, Yuli; Martini, Martini; Kintan, Nabila; Novianti, Nita (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
Currently, ITB Bina Sriwijaya in the academic service process stage still uses manual recording or data processing using Microsoft Excel, this is less effective and efficient so there is a very high risk of losing data in the service process. The method of implementing service includes delivering theoretical and practical material to participants. This community service aims to provide training to all academic members to use Visual 6.0-based academic service applications in managing academic administration services so that they are more efficient, accurate and responsive. The method used in this community service is Service Learning, which is a learning method that emphasizes practical aspects by applying lecture knowledge in the midst of society/community while interacting with society/community and becoming a solution to the problems faced by society. The results of this activity show that participants can understand the concept of academic services through applications using Visual Basic 6.0, operate the software well and realize the importance of digital transformation in the educational administration process. It is hoped that this implementation can improve the quality of administrative services and reduce data management errors.